2016
DOI: 10.1007/s00268-016-3839-9
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Bowel Preparation Does Not Affect Clinical Severity of Anastomotic Leakage in Rectal Cancer Surgery

Abstract: MBP was not found to affect the clinical severity of anastomotic leakage in elective rectal cancer surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…When MBP was compared with no MBP (including no preparation at all and those who underwent a single rectal enema), there was no difference in the incidence of anastomotic leak (OR = 0.90, 95%CI: 0.74 to 1.10, P = 0.32). When MBP vs absolutely no MBP was analysed[ 29 , 40 , 46 , 48 - 50 , 52 , 54 - 65 , 68 , 70 , 71 , 73 ], this made no difference to anastomotic leak rates (OR 0.94, 95% CI 0.70 to 1.25, P = 0.67), nor when MBP was compared with a single rectal enema[ 37 , 45 , 47 , 51 , 53 , 66 , 67 , 69 , 72 , 74 , 76 , 77 ] (OR = 0.92, 95%CI: 0.70 to 1.20, P = 0.52).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…When MBP was compared with no MBP (including no preparation at all and those who underwent a single rectal enema), there was no difference in the incidence of anastomotic leak (OR = 0.90, 95%CI: 0.74 to 1.10, P = 0.32). When MBP vs absolutely no MBP was analysed[ 29 , 40 , 46 , 48 - 50 , 52 , 54 - 65 , 68 , 70 , 71 , 73 ], this made no difference to anastomotic leak rates (OR 0.94, 95% CI 0.70 to 1.25, P = 0.67), nor when MBP was compared with a single rectal enema[ 37 , 45 , 47 , 51 , 53 , 66 , 67 , 69 , 72 , 74 , 76 , 77 ] (OR = 0.92, 95%CI: 0.70 to 1.20, P = 0.52).…”
Section: Resultsmentioning
confidence: 99%
“…When randomised controlled trials alone were included in the analysis[ 37 , 40 , 45 - 65 ] (Supplementary figure 1A), the use of MBP vs no MBP did not affect the incidence of anastomotic leak (OR = 1.02, 95%CI: 0.75 to 1.40, P = 0.90), nor when MBP vs absolutely no MBP[ 40 , 46 , 48 - 50 , 52 , 54 - 65 ] or MBP vs single rectal enema[ 37 , 45 , 47 , 51 , 53 ]were considered. When observational studies alone were analysed[ 66 - 73 , 76 , 77 ] (Supplementary figure 1B), the use of MBP vs no MBP did significantly affect the incidence of anastomotic leak (OR = 0.76, 95%CI: 0.63 to 0.91, P = 0.003), although this was not significant when MBP vs single rectal enema[ 66 , 67 , 69 , 72 , 74 , 76 , 77 ] and MBP vs absolutely no MBP[ 29 , 68 , 70 , 71 , 73 ] were considered separately.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of preoperative mechanical bowel preparation, remains controversial, and a recent review of 1,369 patients who underwent elective rectal cancer resection demonstrated a significantly lower rate of clinical anastomotic leak in the group who had surgery without mechanical bowel preparation [21] . The value of a defunctioning stoma is still not clear.…”
Section: Anastomotic Leakmentioning
confidence: 99%